2016
DOI: 10.2500/ajra.2016.30.4365
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Cleft Computed Tomography Analysis and Olfaction in Chronic Rhinosinusitis

Abstract: Background: Volumetric analysis of the olfactory cleft by using computed tomography has been associated with olfaction in patients with chronic rhinosinusitis (CRS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 19 publications
(25 reference statements)
3
43
1
Order By: Relevance
“…A subset of patients did not undergo CT scan as a part of their clinical care. Cross‐sectional analysis of CT scans was performed using OsiriX MD imaging software (Pixmeo, Bernex, Switzerland), as reported elsewhere . This analysis required specific formatting with thin (0.6‐mm) cut axial, coronal, and sagittal planes for consistency, so some CT scans were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of patients did not undergo CT scan as a part of their clinical care. Cross‐sectional analysis of CT scans was performed using OsiriX MD imaging software (Pixmeo, Bernex, Switzerland), as reported elsewhere . This analysis required specific formatting with thin (0.6‐mm) cut axial, coronal, and sagittal planes for consistency, so some CT scans were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-sectional analysis of CT scans was performed using OsiriX MD imaging software (Pixmeo, Bernex, Switzerland), as reported elsewhere. 18 This analysis required specific formatting with thin (0.6-mm) cut axial, coronal, and sagittal planes for consistency, so some CT scans were excluded. Anterior, middle, and posterior 2-dimensional cross-sectional areas were demarcated in the coronal plane using the axial and sagittal planes for reference of anatomic landmarks.…”
Section: Radiologic Evaluationmentioning
confidence: 99%
“…Still, obstructive processes influence olfactory perception to a great extent in CRS, as reflected by studies on systematic scorings of edema, discharge, scarring, crusting, and polyps of the OC showing correlations with olfactory test results 19,20 . Also, quantifying the degree of opacification of the OC in CRS using computed tomography showed association with olfactory test results 21,22 . Furthermore, in CRS with nasal polyps, obstruction presumably leads to differences in orthonasal and retronasal olfactory function 23 .…”
Section: Discussionmentioning
confidence: 99%
“…20 However, recent studies have challenged this approach. In their series of 107 patients, Adams et al 24 found no difference in cerebrospinal fluid leak recurrence rates between those with (19) and without (88) lumbar drains, irrespective of etiology. Repair technique and defect size (as opposed to body mass index) were the only reported predictors of recurrence.…”
mentioning
confidence: 94%
“…In a prospective clinical study of 62 patients, 46% experienced olfactory deterioration, with significant reduction in threshold, identification, and total smell scores (Connecticut Chemosensory Clinical Research Center olfactory test) up to 1 year after RAI. In addition, Kohli et al 19 examined the relationship between olfactory cleft opacification and olfaction in CRS patients with (12) and without (26) nasal polyposis. Volumetric analysis of the olfactory cleft using computed tomography imaging revealed significant correlations between the degree of opacification and olfactory threshold, discrimination, and identification scores (Sniffin' Sticks test), findings that were more pronounced in the CRS with nasal polyposis group.…”
mentioning
confidence: 99%